The factors contributing to the rise of religious extremism in Malaysia - Akhmetova, Elmira; Aminudin, Rabi'ah; Jaafar, Muhammad Izzuddin (UNISZA, 2020)
This paper aims at analysing the factors contributing to the rise of religious extremism in Malaysia based on a quali-quantitative method using survey data gathered in KL, expert interviews, and secondary literature. It identifies two classes of factors, external and internal, which are contributing to the spread of extremist understanding of religion, including the impact of colonial rule, foreign invasions, politicisation of religion, globalisation, and the consequences of 9/11. It finds that extremism destroys societal wellbeing and national security; thus, any type of extremist ideas and behaviour should be eradicated. It concludes with the recommendations to improve social harmony in Malaysia.